ANALISIS TINGKAT KEBERLANJUTAN PROGRAM KAPAL INKAMINA (30 GT) DI DESA LABUAN BAJO KABUPATEN DONGGALA - Kadir, Hendra (JSTT, 2016)
The research aims at finding out status of sustainable level level on and sensitivity level on Inka Mina Program (30 GT) at Labuan Bajo village Donggala Regency by using Rapfish program. This program used multi-dimension score data. It also used sustainable indicators such as economics, social, ecologic, technology and institutional. The research commenced from April to June 2015 at Labuan Bajo village that already accepting Inka Mina ship (30 GT) with 78 respondents. They consisted of 6 sources, namely: 30 crew of ship, 8 apparatus of marine and Fishery Board and regency, 4 securities, 20 sailormen non Inka Mina and 10 villagers. The research results reveal that sustainable level for of the program generally reachead 70.60 percent. Attribute of sustainable instigator collected and be at positive position showing a high effort stability level. Specifically, it was viewed from each aspect the sustainable level on social aspect reached 85.37 percent with sustainable level of learning, identity, pride, and indicating a high stability. From economics, it was 85.37 percent with attributes such as salary payment period, income, operational cost, acceptance (cashflow), benefits and showing high stability. From technology aspect, it was 73.32 percent with attributes of whorkshop, boat, catching aid devices, device effectiveness, and device appropiateness. On natural resources aspect, it was only 49.74 percent of equipments stock and catching parameter withn attribute of time and sailing distance and stock availability but they alreadymshow high stability. The last aspect, institutional, reached 62.05 percent with attributes of government and non government suport. The government is Marine and Fishery Board while non government is cooperation. Those attributes were already stable. The position Inka Mina Program can be described that social aspect lied on the fifth level, aspects of economics, technology, institutional lied on the fourth level whilw natural resources aspect is on the third level: thus, kite pattern in still abviously seen.